The Americanization of Barbadian English - Stuka, Christine; Justus Liebig University Giessen (My University, 2023)
This paper investigates attitudes and perceptions of Barbadians toward British and American English on the one hand, and the degree of structural Americanization of contemporary Barbadian English as documented in a corpus of Facebook comments on the other hand. The results indicate a discrepancy between explicitly formulated preferences and actual production patterns; while American English is devalued by most respondents, the advancement of cross-linguistic influence of American English on the levels of orthography and lexicon of Barbadian English is undeniable. The findings further suggest a continued linguistic identification with British norms in the perception of many Barbadians, while the awareness of an emerging local standard variety is only slowly gaining ground.
Keywords: ddc:820